2020
DOI: 10.1111/add.15093
|View full text |Cite
|
Sign up to set email alerts
|

On the stability and the progression of gambling problems: longitudinal relations between different problems related to gambling

Abstract: Background and Aims In psychiatric diagnosis, different symptoms of gambling problems are usually aggregated into a single indicator of disorder severity, which has resulted in a knowledge gap on the specific roles of the different issues with which some gamblers struggle. This study estimated the association between baseline symptoms of gambling problems and (i) other symptoms, (ii) the overall severity of gambling problems after 12 months, and the estimated stability rates of various gambling problems after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
(39 reference statements)
1
8
0
2
Order By: Relevance
“…This hypothesis was based on longitudinal studies using survey measures of problem gambling (LaPlante, Nelson, et al, 2008). A recent longitudinal survey study found an inverted-U relationship (Sleczka & Romild, 2021), such that low-and moderate-risk gamblers show more variability in their symptom severity relative to problem gamblers and non-risky gamblers. This is consistent with some of our two-lines tests on raw scores suggesting that positive associations between means and standard deviations level off or reverse directions at higher average risk levels.…”
Section: Interindividual Stability and Intraindividual Change: Are Ma...mentioning
confidence: 99%
“…This hypothesis was based on longitudinal studies using survey measures of problem gambling (LaPlante, Nelson, et al, 2008). A recent longitudinal survey study found an inverted-U relationship (Sleczka & Romild, 2021), such that low-and moderate-risk gamblers show more variability in their symptom severity relative to problem gamblers and non-risky gamblers. This is consistent with some of our two-lines tests on raw scores suggesting that positive associations between means and standard deviations level off or reverse directions at higher average risk levels.…”
Section: Interindividual Stability and Intraindividual Change: Are Ma...mentioning
confidence: 99%
“…Much of the language used by these participants was strongly moralised, and the words 'blame' and 'shame' were used repeatedly in these participants' accounts. Moreover, it has been shown that persecution, tolerance, excessive gambling and guilt (four symptoms of problem gambling) appear to have prognostic validity in the assessment of gambling-related risk (Sleczka & Romild, 2021). Shame was also found to play a mediating role in the relationships between depression and problem gambling (Bilevicius et al, 2018).…”
mentioning
confidence: 99%
“…Consistent with previous research, cited above, it is hypothesised that gambling severity, blame and shame, emotion regulation and gambling motives will be positively correlated with each other. Furthermore, based on the literature reviewed (De Ridder & Deighton, 2021;Jauregui & Estevez, 2019;Schlagintweit et al, 2017;Sleczka & Romild, 2021;Weatherly & Cookman, 2014), it is expected to find that emotion regulation mediates the relationship between gambling severity and shame and blame at the present time and in the past 2 weeks. Finally, the clinical population is expected to show the highest levels of shame and blame (De Ridder & Deighton, 2021), gambling motives (Jauregui et al, 2020) and difficulties in emotional regulation (Marchica et al, 2019;Sancho et al, 2019).…”
mentioning
confidence: 99%
“…El consumo de las cajas botín parece estar asociado a consecuencias negativas en los jugadores (Schwiddessen y Karius, 2018;Zendle et al, 2018;, sin embargo, los efectos específicos, tanto a corto como a largo plazo, todavía no han sido suficientemente estudiados. No obstante, dado que las loot boxes pueden ser consideradas como una forma de juego de azar (Griffiths, 2018), algunas de sus consecuencias podrían ser extrapolables, entre ellas, la culpabilidad (Sleczka y Romild, 2020), la pérdida de control (Moreau, Chauchard, Sévigny y Giroux, 2020) y la sensación de malestar (Oksanen, Savolainen, Sirola y Kaakinen, 2018). En la investigación realizada por Yücel et al (2019) puede encontrarse una revisión pormenorizada de los elementos claves de la adicción.…”
unclassified
“…Específicamente, se hipotetiza que un mayor nivel socioeconómico (Meduna et al, 2019), un mayor número de horas de juego (Li et al, 2019), observar a otros jugadores abrir cajas (King et al, 2018) y la inclusión de nuevos ítems (ej., aspectos de armas, personajes) se asociará con una mayor compra/gasto; y 2) Analizar los efectos del uso abusivo de loot boxes sobre la salud psicoemocional de los jugadores. Concretamente, se plantea que, dadas las similitudes entre las cajas botín y el juego de azar tradicional, los jugadores que compran loot boxes y no obtienen el artículo deseado experimentarán emociones negativas similares a las de los jugadores de azar, como culpabilidad (Sleczka et al, 2020), pérdida de control (Moreau et al, 2020) y sensación de malestar percibido (Oksanen et al, 2018).…”
unclassified